Agents of transnational debate across Europe: The press in emerging European public sphere - Pfetsch, Barbara (Javnost-The Public, 2008)
This article aims at assessing the theoretical and empirical role of the national press in the emerging European public sphere. The study draws on Europeanisation as the emerging framework for transnational communication across European nation states. It assumes that the press itself may perform as a political actor and make a substantial contribution to Europeanisation by advocating European integration and by broadening its scope to include the perspectives of all EU member states and the EU itself. In order to discern the infl uence or role of the media – its “voice” – this study analysed the content of editorials of 28 newspapers in seven European countries along two dimensions. First, the receptiveness of the press towards European perspectives is investigated by measuring the degree to which its editorials feature European scopes. Second, the study examines newspapers’ attitudes about European integration as a political project. The overall findings point to a remarkable representation of European perspectives, and substantial support for EU integration, by the national press in Germany, France, Italy and Spain. The newspapers in the Netherlands and Switzerland were somewhat more parochial, but still supportive. We also see that the United Kingdom (UK) media deviate substantially from these patterns. This study concludes that, in contrast with the findings of earlier studies, the press must be regarded as a signifi cant agent of Europeanisation fostering transnational linkages of public debate.